2022
DOI: 10.3390/buildings12071001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Crumb Rubber and Coconut Coir on Strength and Durability Characteristics of Interlocking Paving Blocks

Abstract: Interlocking Paving Blocks (IPB) are, nowadays, a widely used construction material. As a result of the surge in demand for IPBs, alternative materials have been investigated to be used for IPBs. This study investigated the strength and durability characteristics (compressive strength, split tensile strength, density, water absorption, skid resistance, and abrasion resistance) of IPBs in the presence of (waste materials) crumb rubber (CR) and coconut coir fibers (CCF). Both compressive and split tensile streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Although this observed abrasion volume loss of the concrete paving block falls within the ASTM C936 [34] specifications, the char-based paving block has less thickness loss indicating a better resistance during traffic abrasion than the concrete paving block depicted in Figure 12. Additionally, when developing paving blocks, Gamage et al [50] considered the use of coconut coir and crumb rubber. With a 5% crumb rubber content, they found that the abrasion resistance had improved by over 7% when compared to the control sample.…”
Section: Abrasion Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Although this observed abrasion volume loss of the concrete paving block falls within the ASTM C936 [34] specifications, the char-based paving block has less thickness loss indicating a better resistance during traffic abrasion than the concrete paving block depicted in Figure 12. Additionally, when developing paving blocks, Gamage et al [50] considered the use of coconut coir and crumb rubber. With a 5% crumb rubber content, they found that the abrasion resistance had improved by over 7% when compared to the control sample.…”
Section: Abrasion Resistancementioning
confidence: 99%
“…resistance during traffic abrasion than the concrete paving block depicted in Figure 12. Additionally, when developing paving blocks, Gamage et al [50] considered the use of coconut coir and crumb rubber. With a 5% crumb rubber content, they found that the abrasion resistance had improved by over 7% when compared to the control sample.…”
Section: Abrasion Resistancementioning
confidence: 99%
“…Thus far, sidewalks, bike lanes, residential road entrances, parking lots, industrial zones, ports, airports, and permeable areas have all been built using concrete block pavement (Mascio et al, 2019;Research et al, 2019). Concrete block paving roads have emerged as an intriguing and cost-effective substitute for stiff and flexible sidewalks (Gamage et al, 2022;Widayanto et al, 2019). Concrete block pavement is attractive for various residential, commercial, municipal, and industrial situations and sites such parking lots, pedestrian crossings, traffic intersections, and roadways because of its strength, durability, and surface aesthetics.…”
Section: Introductionmentioning
confidence: 99%
“…Then, research that evaluated the application of CDW recycled aggregates [25,26] and fibers [27,28] in concrete can be cited in Brazil and Portugal. Furthermore, studies in China [29], Turkey [30], Indonesia [31], and Sri Lanka [32] can also be cited. Therefore, by-products from different sources can be used in engineering works by determining the most appropriate concrete mixture for CPBs.…”
Section: Introductionmentioning
confidence: 99%